The effect of Fourplex® on gain and health of newly arrived calves - F.K. Brazle; Gerald L. Stokka (Kansas Agricultural Experiment Station Research Reports, 1994)
Two trials were conducted to evaluate the effects of Fourplex®, a trace mineral supplement, on long-hauled stocker calves. In each trial, Fourplex was added to the ration of lightweight, long-hauled calves in four pens, while calves in another four pens served as controls. Additionally, every other calf that became sick, regardless of feed treatment, was drenched with a solution of Fourplex in Trial I and a Cu, Zn, Mn+Co solution in Trial II. Fourplex in the feed did not improve ADG, reduce morbidity, or reduce the number o f treatments required per sick animal. In Trial II , Fourplex-fed calves that became sick required more treatments (P<.12) during the first 2 weeks; however, during the third and fourth weeks, they required fewer treatments (P<.03). In Trial I, sick calves drenched with Fourplex required more treatments. In Trial II, drenching with a Cu, Zn, Mn+Co solution resulted in an increase in treatments per sick calf during the fourth week. In these trials, Fourplex did not significantly increase performance or reduce sickness.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Fourplex®; Copper; Zinc; Trace minerals